Preconditioned human dental pulp stem cells with cerium and yttrium oxide nanoparticles effectively ameliorate diabetic hyperglycemia while combatting hypoxia. (December 2021) - Ahmed, Hanaa H.; Aglan, Hadeer A.; Mahmoud, Nadia S.; Aly, Riham M.
Graphical abstract: Highlights: Human dental pulp stem cells can efficiently differentiate into insulin-producing cells in the presence of CeO2 and Y2 O3 nanoparticles. The most prominent anti-diabetic potential of the transplanted IPCs was exerted in combination with CeO2 . Generated IPCs were able to home into injured pancreas after systemic implantation and succeeded in controlling blood glucose. Human dental pulp stem cells forecasts a promising role in the future of stem cell based-therapies for the treatment of diabetes. Abstract: The development of efficient insulin producing cells (IPC) induction system is fundamental for the regenerative clinical applications targeting Diabetes Mellitus. This study was set to generate IPC from human dental pulp stem cells (hDPSCs) capable of surviving under hypoxic conditions in vitro and in vivo. Methods: hDPSCs were cultured in IPCs induction media augmented with Cerium or Yttrium oxide nanoparticles along with selected growth factors & cytokines. The generated IPC were subjected to hypoxic stress in vitro to evaluate the ability of the nanoparticles to combat hypoxia. Next, they were labelled and implanted into diabetic rats. Twenty eight days later, blood glucose and serum insulin levels, hepatic hexokinase and glucose-6-phosphate dehydrogenase activities were measured. Pancreatic vascular endothelial growth factor ( VEGF ), pancreatic duodenal homeobox1 ( Pdx-1 ), hypoxia inducible factor 1 alpha ( HIF-1α ) and Caspase-3 genes expression level were evaluated. Results: hDPSCs were successfully differentiated into IPCs after incubation with the inductive media enriched with nanoparticles. The generated IPCs released significant amounts of insulin in response to increasing glucose concentration both in vitro & in vivo . The generated IPCs showed up-regulation in the expression levels of anti-apoptotic genes in concomitant with down-regulation in the expression levels of hypoxic, and apoptotic genes. The in vivo study confirmed the homing of PKH-26-labeled cells in pancreas of treated groups. A significant up-regulation in the expression of pancreatic VEGF and PDX-1 genes associated with significant down-regulation in the expression of pancreatic HIF-1α and caspase-3 was evident. Conclusion: The achieved results highlight the promising role of the Cerium & Yttrium oxide nanoparticles in promoting the generation of IPCs that have the ability to combat hypoxia and govern diabetes mellitus.